High-dose-rate intracavitary brachytherapy boost post-external beam radiotherapy using rotterdam’s applicator in a case of recurrent carcinoma nasopharynx (Indian Journal of Case Reports, 2019)
Long-term local control is possible in a highly radio-responsive tumor-like carcinoma of the nasopharynx, even in the recurrent setting. High-dose-rate brachytherapy boost with its steep dose fall-off helps achieve salvage by providing optimal dose coverage to the tumor volume which is in close anatomic proximity to critical structures at the base of the skull. Here, we report the case of a 58-year-old lady, an old case of carcinoma nasopharynx presented with recurrence of symptoms in the form of nasal blockade along with a right pre-auricular swelling. Further evaluation showed an fluorodeoxyglucose-avid nasopharyngeal mass, a biopsy from which was positive for nasopharyngeal carcinoma (NPC). She first received re-radiation with external beam radiotherapy using 6 MV photons to the face and neck along with concurrent chemotherapy with cisplatin followed by brachytherapy boost with Rotterdam’s Brachytherapy Applicator @5 Gray×2# 1 week apart. Brachytherapy is a feasible tool that allows dose escalation to achieve long-term tumor control in locally advanced NPCs.